Replication of DNA templates containing 5-formyluracil, a major oxidative lesion of thymine in DNA. - Zhang, Q M (1997)
5-Formyluracil (5-foU) is a major lesion of thymine produced in DNA by ionizing radiation and various chemical oxidants. To assess its biochemical effects on DNA replication, 22mer oligonucleotide templates containing an internal 5-foU at defined sites were synthesized by the phosphoramidite method and examined for ability to serve as a template for various DNA polymerases in vitro . Klenow fragments with and without 3'-->5'exonuclease of DNA polymerase I, Thermus thermophilus DNA polymerase (exonuclease-deficient) and Pyrococcus furiosus DNA polymerase (exonuclease-proficient) read through the site of 5-foU in the template. Primer extension assays revealed that the 5-foU directed not only incorporation of dAMP but also dCMP opposite the lesion during DNA synthesis. Misincorporation opposite 5-foU was unaffected by 3'-->5' exonuclease activity. DNA polymerases had different dissociation rates from a dCMP/T mispair and from a dCMP/5-foU mispair. The incorporation of an 'incorrect' nucleotide was dependent on the sequence context and DNA polymerase used. These results suggest that 5-foU produced in DNA has mutagenic potential leading to T-->G transversions during DNA synthesis.